اكتشاف فعالية الوسائل التعليمية لتعليم اللغة العربية للناطقين بغيرها في جمهورية إندونيسيا: الجامعة الحكومية مالانج بإندونيسيا نموذجا - Ahmad Yani bin Imam Shabari, Siti Sara bint Haji Ahmad (CMES (Center of Middle Eastern Studies), 2019)
This study aims to identify the positive and negative sides of the applied Arabic learning media in Indonesia. The State University of Malang (UM) was chosen as a sample learning model since it has been a well-known university for the Arabic language and has considerable attention to Arabic language issues in Indonesia. This study was designed with quantitative and evaluative methods in the data display and analysis of this study. The researcher collected the research data by distributing questionnaires to both lecturers and students of the State University of Malang with regard to the learning media used, then the researchers evaluated the Arabic learning facilities with the Arabic learning communication approach to non-Arabic and applied the quantitative evaluative method. The results of the analysis concluded that the use of Arabic learning media at the UM Malang reflects both positive and negative sides.